INOVASI MODEL PEMBELAJARAN LITERASI DIGITAL DENGAN BANTUAN KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) UNTUK MEWUJUDKAN SDGs 2030 - Sely Trianie; Elsa Safitri; Ichsan Fauzi Rachman (Kampus Akademik Publiser, 2024)
The digital era demands adequate digital literacy skills for society. The 2030 Sustainable Development Goals (SDGs) emphasize the importance of digital literacy to achieve various targets, including access to information and education, economic empowerment, and civic participation. This article examines the optimization of digital literacy learning models with the help of artificial intelligence (AI) to realize SDGs 2030. This artificial intelligence offers various potentials to increase the effectiveness of digital literacy learning, such as personalization of learning, content adaptation, and automatic assessment. Therefore, this article discusses strategies for implementing AI in digital literacy learning models, including choosing the right AI technology, designing effective learning models, and integrating AI with traditional learning methods.